Faber Polynomial Expansion for a New Subclass of Bi-univalent Functions Endowed with (p,q) Calculus Operators - Ahuja, Om P.; ÇETİNKAYA, ASENA (Fuat Usta, 2021)
In this paper, we use the Faber polynomial expansion techniques to get the general TaylorMaclaurin coefficient estimates for |an|, (n ≥ 4) of a generalized class of bi-univalentfunctions by means of (p,q)−calculus, which was introduced by Chakrabarti and Jagannathan. For functions in such a class, we get the initial coefficient estimates for |a2| and|a3|. In particular, the results in this paper generalize or improve (in certain cases) thecorresponding results obtained by recent researchers.
Keywords: Bi-univalent Functions; Faber Polynomial Expansion; (p; q)−Calculus